2013
DOI: 10.1149/05007.0139ecst
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Cu-Cu Wafer Bonding

Abstract: Metal thermo-compression bonding is a process suitable for 3D interconnects applications at wafer level. The process requires typically bonding temperatures of ~400°C and high contact pressure applied during bonding. Temperature reduction below such values is required in order to solve some issues regarding wafer-to-wafer misalignment after bonding and to minimize thermo-mechanical stresses. Low-temperature (LT) Cu-Cu wafer bonding was successfully demonstrated at 175°C. The bond quality, bond strength, metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…In previous work (4,9) the surface copper oxide was identified using XPS as being CuO. Further, using the same technique as well as high-resolution TEM, it was proven that CuO could be successfully removed from the surfaces.…”
Section: Surface Cleanlinessmentioning
confidence: 95%
“…In previous work (4,9) the surface copper oxide was identified using XPS as being CuO. Further, using the same technique as well as high-resolution TEM, it was proven that CuO could be successfully removed from the surfaces.…”
Section: Surface Cleanlinessmentioning
confidence: 95%
“…Another available method of copper-to-copper bonding is thermocompression bonding (TCB). Copper wafers are bonded and annealed at approximately 400°C to remove copper oxide (Rebhan et al , 2013), and Cu atom interdiffusion achieves grain growth and interface disappearance (Chen et al , 2002; Chen et al , 2003). Excessively high temperatures (∼400°C) damage the electronic circuit structure and cause the potential failure (Tang et al , 2012).…”
Section: Wet Treatment and Plasma-assisted Bondingmentioning
confidence: 99%
“…Since the Cu surface was all exposed to the air and treated by water in the bonding process, there was inevitable Cu 2 O layer formation on the Cu surface for all samples. 29,30) Yet it is reported that Cu 2 O would decompose to Cu and O at temperatures higher than 180 °C. 31) Because the Cu dishing (−3.17 nm) of S1 was less than the Cu expansion [5.313 nm @ (25 °C-200 °C), 9.687 nm @ (25 °C-350 °C)], the Cu-Cu interface was well contacted and Cu-Cu diffusion bonding could happen at 200 °C in the first-step annealing.…”
Section: Bonding Surface Study After Furnace Annealingmentioning
confidence: 99%